TUNGSTEN ISOTOPES AND THE EARLY DEVELOPMENT OF THE EARTH AND MOON - Halliday A.N.; Lee D.C. (My University, 1999)
The rates of accretion and core formation of the Earth and other inner solar system objects can be effectively studied using the newly developed 182Hf-182W chronometer. This approach offers far more leverage than any other short-lived nuclide system because: 1. the half-life of 9 Myrs is ideal for accretionary timescales; 2. both parent and daughter elements are highly refractory and in known, chondritic proportions in the Earth; 3. the initial 182Hf atomic abundance at the start of the solar system was relatively high; and 4. Hf and W are strongly fractionated by the early processes of melting and core formation.